Symbiotic Relation between a Library and an Academic Institution - Gautam, Sarita (Access: An International Journal of Nepal Library Association, 2023)
Academic libraries and academic institutions are always interlinked and dependent on the purpose of serving educational activities and the well-designed curriculum of the formal education system. Academic institutions without a library have no significance and an academic library without its parent institution has no origin. But it is rarely found that these are named, discussed, analyzed, and worked together as a whole. This study aimed to find out the academicians’ perceptions of the symbiotic relationship between academic institutions and libraries. For the study, the Central Departments of the University Campus Tribhuvan University, Nepal were chosen. The study followed the quantitative method using a survey research design through a questionnaire tool eleven responses were received. Data were analyzed descriptively. Academicians have a keen interest in the establishment of libraries within the department and arrange the library scientifically to enhance research and teaching learning activities. In most of the departmental libraries the post of librarian was found vacant. The praiseworthy dedication of the academicians to the development of libraries for their collaborative partnership was found. They are very much sure about the impact of libraries in teaching learning and research activities. The service delivered by the libraries as the first door to the search for information bystudents and faculties is recommended undoubtedly.